Blockchain-Driven Business Model Innovation for Trade Finance Platform Ecosystems - Poczos, Barnabas; Chen, Lin (Journal of Computer Science and Software Applications, 2024)
The rapid expansion of trade finance and the transformative impact of advanced information technologies have stimulated the emergence of digital trade finance platforms. Traditional business models within trade finance ecosystems are increasingly unable to meet the operational demands of these platforms, creating an urgent need for innovation. This study examines the structural components of trade finance platform ecosystems and explores how blockchain technology enables new forms of business model innovation. Guided by the value triangle theory, the research analyzes platform architecture, operational mechanisms, and profitability models. The findings uncover how blockchain reshapes trade finance platform ecosystems and outline practical pathways for implementing blockchain-enabled business model innovation.